Convenient Access to Hydroquinone and Quinone Derivatives from Cyclobutenedione Units - Nguyen, Thanh Vinh (CSIRO Publishing, 2010)
Thirty years ago, cyclobutenediones were only studied as theoretically interesting molecules without much thought towards their potential use in building complex structures.[1–3] Late in the 1980s, these compounds started to find their way into synthetic organic chemistry via their conversion to highly functionalized benzoquinones and cyclopentenones.[1] During the studies of unsaturated ketenes,[4,5] Moore and coworkers discovered one of the most important uses of cyclobutenediones while carrying out the thermolysis of 4-alkynyl-4-hydroxycyclobutenones. These compounds were able to undergo 4p-electrocyclic ring opening to the corresponding enynylketenes, which subsequently ring close to formdiradical intermediates. These intermediates then rearrange to formquinone or hydroquinone derivatives via either radical addition or homolytic substitution, offering a convenient synthetic method to access polycyclic compounds containing quinone/hydroquinone moieties from cyclobutenediones.[4–20]